PENERAPAN MODEL DISCOVERY LEARNING BERBANTUAN MEDIA WARDAH ( WARUNG DATA HIDANGAN KESUKAAN) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI DIAGRAM TURUS PADA MURID KELAS II UPT SDN SENDANGHARJO IV - Rohmatus Sholiha Septiana; Sumadi; Sri Wahyun (STKIP Subang, 2026)
This study explores the effectiveness of implementing the Discovery Learning model assisted by the WARDAH (Warung Data Hidangan Kesukaan / Favorite Food Data Stall) learning media in improving students mathematics learning outcomes on the topic of tally charts among students II class at UPT SDN Sendangharjo IV..This research is a Classroom Action Research (CAR) design conducted in two cycles involving 35 students of II class at UPT SDN Sendangharjo IV Data were collected through classroom observations, learning achievement tests, and document analysis, while the data is analyzed using a descriptive quantitative approach. In cycle revealed that the implementation of the Discovery Learning model assisted by the WARDAH learning media significantly improved mathematics learning outcomes. In Cycle I, the students' average score reached 74.03, with a classical learning mastery of 42.86%. In Cycle II, the average score increased to 86.23, while the classical learning mastery improved to 92.24%. in conclusion the implementation of the Discovery Learning model assisted by the WARDAH learning media is effective to improving students class II mathematics learning outcomes at UPT SDN Sendangharjo IV.